2013
DOI: 10.1111/codi.12218
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic disease of the colon: systematic review

Abstract: Diaphragm disease of the colon is a rare condition associated with long-term use of NSAIDs with a range of presentations and symptoms. Based on this review, when colon diaphragm disease is diagnosed we would recommend a trial cessation of NSAIDs. Therapeutic endoscopic techniques should be considered but surgery may be required for definitive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
(28 reference statements)
1
17
0
Order By: Relevance
“…The amount of diclofenac that the patient had used, as well as the duration of the drug use account for the biological gradient (the presence of a dose-response relationship) and the temporality, as previously stated by Aftab et al 6 . Finally, the recovery of the eroded colonic mucosa after cessation of diclofenac acts as experimental evidence, in accordance with the suggestion that trial cessation of the NSAIDs should be implemented in the presence of colonic diaphragms 1 . One of the most frequent tools used in adverse drug reaction assessment is the Naranjo probability scale, featuring a list of weighted questions related to the presence of previous reports on a specific reaction, the temporal relationship between the drug and the effect, alternative causes for the event, previous reactions to the same drug, as well as the drug dosage.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The amount of diclofenac that the patient had used, as well as the duration of the drug use account for the biological gradient (the presence of a dose-response relationship) and the temporality, as previously stated by Aftab et al 6 . Finally, the recovery of the eroded colonic mucosa after cessation of diclofenac acts as experimental evidence, in accordance with the suggestion that trial cessation of the NSAIDs should be implemented in the presence of colonic diaphragms 1 . One of the most frequent tools used in adverse drug reaction assessment is the Naranjo probability scale, featuring a list of weighted questions related to the presence of previous reports on a specific reaction, the temporal relationship between the drug and the effect, alternative causes for the event, previous reactions to the same drug, as well as the drug dosage.…”
Section: Discussionsupporting
confidence: 77%
“…These viewpoints are regarded as criteria for identifying causality in clinical practice even beyond epidemiological studies 10 . Despite the fact that NSAID-induced colopathy is a rare event (yielding a small number of reports in the literature), the systematic review by Munipalle et al provided an optimistic basis for future research on the strength of association between NSAID use and colonic lesions 1 . The existence of several case reports and case series (which have been referenced in this paper) account for the consistency of this association, while the plausibility and coherence can be estimated with the knowledge of NSAID metabolism, despite the fact that the pathophysiology of colopathy is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the increasing use of slow-release and enteric-coated NSAIDs that allow more drugs to reach the colon, their influence has come to the attention of researchers. In a systematic review that analysed 45 patients diagnosed with an NSAID-induced colopathy, Munipalle et al [5] reported diclofenac as the causative agent in most of these cases, wherein the median usage of NSAIDs was 5 years. As the gut has a narrow set of responses, the outcome is inflammation, ulceration, and the formation of fibrous diaphragm-like strictures as a result of healing [6].…”
Section: Discussionmentioning
confidence: 99%
“…Originally described in terminal ileum, 4 it has also been reported in right colon. 5 The diagnosis is straightforward on endoscopy and gross examinations of resected specimens. Histologically, elongated plicae (diaphragms) with submucosal fibrosis are seen, often eroded at the tip.…”
Section: Most Common Drug-induced Histologic Patterns Of Injury In Comentioning
confidence: 99%